Measuring the Level of Scientific Reasoning Ability of Biology Prospective Teachers - Laras Firdaus; Masiah Masiah; Ibrohim Ibrohim; Sri Rahayu Lestari (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This research is quantitative survey research that aims to identify the level of scientific reasoning ability of Biology prospective teachers, as well as to determine the effect of the semester on scientific reasoning abilities. A total of 80 Biology prospective teachers were involved in this study, consisting of 18 (semester 2), 29 (semester 4), and 33 (semester 6). LCSTR is an instrument used to measure scientific reasoning ability. The data were analyzed descriptively to classify the level of scientific reasoning ability, while to determine the effect of the semester on scientific reasoning ability, it was analyzed univariately using SPSS 22 at a significance level of 5%. The results of this study indicate that the scientific reasoning ability of Biology prospective teachers is dominated by concrete and transitional reasoning, and semesters have no effect on scientific reasoning abilities. These results also indicate that Biology prospective teachers have the same level of scientific reasoning ability. Furthermore, these results can be concluded that the scientific reasoning ability of Biology prospective teacher students has a low level, which is at the initial level (concrete reasoning). Then for the further work, it is described a little at the conclusion of this article.